Endovascular aortic repair endograft limb misdeployment salvaged with laser fenestration - Mira T. Tanenbaum, MD; Andrea E. Klein, MD; Jacqueline L. Babb, MD; Mirza S. Baig, MD; Melissa L. Kirkwood, MD; Carlos H. Timaran, MD (Journal of Vascular Surgery Cases and Innovative Techniques)
Endovascular aortic aneurysm repair (EVAR) offers a minimally invasive treatment approach for abdominal aortic aneurysms (AAAs). Iliac limb misdeployment outside of the gate is a rare complication that traditionally requires open conversion. We describe two cases of limb misdeployment salvaged with in situ laser fenestration (ISLF). An ISLF was created through the misplaced iliac limb into the aneurysm sac, allowing for subsequent gate cannulation. A new limb was then deployed from the gate through the fenestration into the iliac artery. These cases demonstrate that ISLF through a misdeployed EVAR limb is a novel bail-out endovascular technique that circumvents open surgery and restores the aortoiliac anatomic continuity of the repair.